2015
DOI: 10.1111/hpb.12315
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic microwave ablation of human liver tumours using a novel three-dimensional magnetic guidance system

Abstract: The AIM™ guidance system is an effective adjunct for laparoscopic ablation. It facilitates a high degree of accuracy and a good first-attempt success rate, and avoids the line of site interference associated with infrared systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…The morbidity in these studies has ranged from 0 to 60 % and mortality 0-2 % [6,[19][20][21]. The current study, with no morbidity or mortality via a predominantly laparoscopic approach, compares favorably with these reports.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The morbidity in these studies has ranged from 0 to 60 % and mortality 0-2 % [6,[19][20][21]. The current study, with no morbidity or mortality via a predominantly laparoscopic approach, compares favorably with these reports.…”
Section: Discussionsupporting
confidence: 53%
“…In the literature, different authors have reported on open [7,[16][17][18], percutaneous [6,19] and laparoscopic [20,21] applications of MWA for various malignant liver tumors. The morbidity in these studies has ranged from 0 to 60 % and mortality 0-2 % [6,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity of MWA ranges between 0–60% and mortality 0–2% in the literature where the procedure was performed via an open , percutaneous , or laparoscopic procedure for various malignant liver tumors. Our results, with no mortality and 11% morbidity via a predominantly laparoscopic approach, compare favorably with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…There were 45 ablations performed on 34 tumors in 13 patients, the median number of lesions per patient was 2, and the median lesion size was 1.7 cm. 56 The success rate of first-attempt central targeting was 93%; 3 lesions required 2 passes each, and targeting was independently verified by a radiologist reviewing preoperative CTs or MRIs as well as ultrasound images from the procedure. 56 The subjective ease with which the tumors were targeted were also scored, something quite unique in the literature, and again the results were promising.…”
Section: Electromagnetic Tracking Systemsmentioning
confidence: 99%